Αναβάθμιση βιοαερίου σε βιομεθάνιο με χρήση αναερόβιας βιομάζας και σιδήρου μηδενικού σθένους - Χρυσάνθου, Γεωργία (Τμήμα Επιστήμης και Τεχνολογίας Περιβάλλοντος, Σχολή Γεωτεχνικών Επιστημών και Διαχείρισης Περιβάλλοντος, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2018)
In this thesis a laboratory study was carried out on the biogas upgrading in biomethane using anaerobic biomass and zero valence iron. Biogas consists mainly of methane and carbon dioxide, where other substances (humidity, ammonia, etc.) are present in small quantities. With its upgrading, an increase in the methane ratio of up to 98% in purity is achieved, with existing technologies being based on natural gas and gas, resulting in the upgrading of upgraded biogas to become a fuel of high energy value. When the content of the upgraded biogas in methane is over 80% and the amount of carbon dioxide 2-3% then it can be spilled into the natural gas network or used as a transport fuel. The purpose of this study was to achieve the upgrading of biogas by using cheap materials or even materials of negative value (iron waste). When using zero valence iron, oxidation is achieved by the simultaneous production of hydrogen, which is consumed together with carbon dioxide by Hydrogenotrophic Methanogens to produce methane. Four laboratory experiments were carried out, where the first tested the biogas upgrading capacity using commercial iron at various concentrations with the highest yield occurring during the increase in iron concentration. In the second laboratory experiment, the performance of different types of iron waste, spiral, crushed and dust was tested at a concentration of 150 g / L, with the addition of 5 g of anaerobic sludge where on day 15 an increase in methane up to 97% was observed in the spiral. The third laboratory experiment was followed by the second, where the samples containing the crushed iron were removed and in place commercial iron solutions were made. The remaining solutions were removed 20 mL of liquid replaced with 20 mL of Angelidaki BioMedicine where no increase in methane was observed as opposed to commercial iron containing solutions where the iron content reached 97% at seven days. In the last laboratory experiment, two glass bottles were used to try to create two bioreactors (approximate conditions) that would be joined together with a small internal diameter silicone tube. The aim of this project was to produce biogas in the first bioreactor which would be transported to the second where the biogas would be upgraded to biomethane. This target has been achieved to a certain extent, but research needs further study as this experiment was the first approach.
Keywords: Anaerobic digestion; Biogas; Biomethane; Biogas upgrading; Zero-valence iron; Αναερόβια χώνευση; Βιοαέριο; Βιομεθάνιο; Αναβάθμιση βιοαερίου; Σίδηρος μηδενικού σθένους